1989
DOI: 10.1007/bf01963456
|View full text |Cite
|
Sign up to set email alerts
|

Unusual in vitro formation of cyst-like structures associated with human intestinal spirochaetosis

Abstract: Spirochaetes were isolated from rectal biopsies of three patients and successfully cultured. Enzymatic reactions and electron microscopy revealed spirochaetes resembling Brachyspira aalborgi. Examination of ultrathin sections of centrifugates of cultured spirochaetes yielded unusual cyst-like structures with an outer double membrane containing spirochaetes in different developmental stages. The protoplasmic cylinders seemed to originate from a large electron-dense focus in the cyst-like structures. The axial f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
0
7
0
1
Order By: Relevance
“…For example B. pilosicoli has been recovered from lake water and wild waterbirds, both of which could be sources of human infection (Oxberry et al, 1998). Under adverse conditions B. pilosicoli can assume a resistant cyst-like structure (Gebbers and Marder, 1989;Barber et al, 1995), and this may aid its survival outside the intestinal tract.…”
Section: Brachyspira (Serpulina) Pilosicolimentioning
confidence: 99%
“…For example B. pilosicoli has been recovered from lake water and wild waterbirds, both of which could be sources of human infection (Oxberry et al, 1998). Under adverse conditions B. pilosicoli can assume a resistant cyst-like structure (Gebbers and Marder, 1989;Barber et al, 1995), and this may aid its survival outside the intestinal tract.…”
Section: Brachyspira (Serpulina) Pilosicolimentioning
confidence: 99%
“…HIS is a morphological description based on microscopic examination of biopsy samples. Hence, most reports have outlined histologic and electron microscopic findings, whereas there have been only a few reports of concurrent culturing of spirochetes from the same individuals (11,15,17,36), and two species, Brachyspira aalborgi and Brachyspira (Serpulina) pilosicoli, have been identified (17,36).Recently, the phylogeny of intestinal spirochetes has been studied by multilocus enzyme electrophoresis (20, 21), polyacrylamide gel electrophoresis (7), pulsed-field gel electrophoresis (6, 29), and 16S rRNA gene sequencing (13); these studies have revealed considerable heterogeneity among human isolates. However, it seems that human intestinal spirochetes can be separated into at least two groups: a heterogeneous group closely related to or indistinguishable from B. pilosicoli and a second group consisting of the type strain of B. aalborgi (13,20).…”
mentioning
confidence: 99%
“…Ultrastructurally, spirochetes are attached perpendicular to the epithelial membrane between the microvilli, which appear shorter or depleted (11,17,23,36). However, more severe lesions with spirochetal invasion of the epithelium and the adjacent lamina propria together with purulent discharge may occur (15,27,30,42). HIS is a morphological description based on microscopic examination of biopsy samples.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Histologic analysis of intestinal biopsy specimens showed densely packed spirochetes attached by 1 end to colonic epithelium, forming a false brush border (11). Invasion of colonic epithelial cells and bleeding may occur (4,12). Virulence mechanisms remain poorly understood.…”
mentioning
confidence: 99%